Analisis Perbandingan Nilai SAW dan TOPSIS dalam Menentukan Keputusan Perjalanan Wisata ke Destinasi Wisata Tematik - Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to process information related to ticket costs, facilities, safety, cleanliness, road access, and mileage using the Simple Additive Weighting (SAW) method and Technique for Other Preferences by Similarity to Ideal Solution (TOPSIS) in the selection of natural tourism destinations, cultural tourism, beach, and marine tourism based on the context of North Halmahera Regency. The weights on each criterion that have been determined in the SAW method are as follows: ticket fee (0.30); facilities (0.30); security (0.30); cleanliness (0.30); access roads (0.30); mileage (0.30). Meanwhile, the weights on each criterion that have been determined according to the degree of importance in the TOPSIS method are as follows: ticket fees (5); facilities (4); security (3); cleanliness (3); access roads (3); mileage (3). Based on the results of the implementation of the SAW method in the selection of thematic tourist destinations, it can be seen that: based on the context of natural and adventure tourism destinations, Telaga Paca (A2) tourist destinations occupy the first position with a value of 0.903333; based on the context of historical and cultural tourist destinations, Hibualamo tourist destinations (B6) observed the first position with a value of 0.975; based on the context of beach and recreation tourism destinations, Pitu Beach tourist destinations (C1) occupy the first position with a value of 0.804167; based on the context of marine tourism destinations in the archipelago, Kumo Island tourist destinations (D2) occupy the first position with a value of 0.946429. Meanwhile, the results of the implementation of the TOPSIS method show that: based on the context of natural and adventure tourism destinations, Telaga Paca (A2) tourist destinations occupy the first position with a value of 0.74523053; based on the context of historical and cultural tourist destinations, Duma Village tourist destinations (B1) observe the first position with a value of 0.86431018; Based on the context of beach and leisure tourism destinations, tourist destinations Tanjung Pilawang (C7) occupies the first position with a value of 0.85054074; based on the context of marine tourism destinations in the archipelago, Magaliho Island tourist destinations (D7) occupy the first position with a value of 0.74142938